Participatory Strategic Planning for Sustainable Agrotourism Development in Buluh Nipis Village - Sufian Hamim; Fabellany Sovina (Mandalika Journal of Business and Management Studies, 2026)
Despite its abundant natural resources, strong Islamic values, and rich Malay cultural heritage, Buluh Nipis Village has not yet realized its agrotourism potential because development planning remains predominantly top-down with limited community participation. This study addresses this gap by analyzing a participatory strategic planning approach for sustainable agrotourism development. A mixed-methods design was employed, integrating quantitative and qualitative approaches through surveys, collaborative participatory research, structured interviews, questionnaires, observations, and document analysis. Purposive sampling was used to select the research site, respondents, and informants, involving a total of 100 participants. The findings reveal that community participation remains low (50%) due to the dominance of top-down planning (60%), although respondents perceive the village's agrotourism potential to be very high (85%). These results indicate the need to transform conventional planning into a participatory model that actively involves local communities in decision-making and development processes. The study proposes a strategic planning model that integrates local natural resources, Islamic values, Malay cultural wisdom, and food security into a unified framework for sustainable agrotourism development. This integrated model constitutes the study's principal contribution by providing a context-based planning framework that strengthens community participation, supports rural economic development through BUMDes, promotes digital village planning, and enhances tourism branding rooted in local identity.